2021
DOI: 10.1038/s41598-021-00366-8
|View full text |Cite
|
Sign up to set email alerts
|

ANXA2 is correlated with the molecular features and clinical prognosis of glioma, and acts as a potential marker of immunosuppression

Abstract: Recent studies have shown that ANXA2 is important in the development of many cancers, while its role in glioma-related immune response remains unclear. We aimed to comprehensively investigate its biological characteristics and clinical value in glioma. We analyzed 699 glioma samples from The Cancer Genome Atlas as training cohort and 325 samples from the Chinese Glioma Genome Atlas as validation cohort. All the statistical analyses and figures were generated with R. ANXA2 was overexpressed significantly in hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In the last few years, TCGA network have divided gliomas into four molecular subtypes: proneural, neural, classical and mesenchymal type 36 . This classification has been proved to be meaningful for patients’ survival status, especially mesenchymal subtype which is representing for invasion and poor prognosis 5 . So, we analyzed the relationship between CTSB and TCGA subtypes.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the last few years, TCGA network have divided gliomas into four molecular subtypes: proneural, neural, classical and mesenchymal type 36 . This classification has been proved to be meaningful for patients’ survival status, especially mesenchymal subtype which is representing for invasion and poor prognosis 5 . So, we analyzed the relationship between CTSB and TCGA subtypes.…”
Section: Resultsmentioning
confidence: 99%
“…In the results above, it is suggested that CTSB is related with the inflammatory response of gliomas, so in order to explore the function of CTSB, we analyzed 104 inflammatory genes which could be divided into seven metagenes 5 . Supplementary Table S3 summarizes the detailed list of these genes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations